2016
DOI: 10.1902/jop.2015.150235
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Radiographic Periodontal Status Between Habitual Water‐Pipe Smokers and Cigarette Smokers

Abstract: Males in a Saudi Arabian community who were CSs or WPs had more MT and poorer periodontal condition than never smokers. The periodontal condition of WPs was equally as poor as CSs. Additional clinical observational studies with emphasis on sex and sociodemographic characteristics are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(138 citation statements)
references
References 40 publications
12
121
5
Order By: Relevance
“…This hypothesis was based results from previous clinical studies in which, oral soft tissue inflammation and alveolar bone loss (ABL) around natural teeth and dental implants was shown to be significantly higher among CS compared with NS. 7,16,19,20 Moreover, tobacco smoking increases the AGES-RAGE interactions thereby increasing the production of destructive inflammatory cytokines, such as IL-6 and IL-1b. 10,11 Increased levels of these cytokines in the oral fluids have been associated with the etiology of periodontal and peri-implant diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was based results from previous clinical studies in which, oral soft tissue inflammation and alveolar bone loss (ABL) around natural teeth and dental implants was shown to be significantly higher among CS compared with NS. 7,16,19,20 Moreover, tobacco smoking increases the AGES-RAGE interactions thereby increasing the production of destructive inflammatory cytokines, such as IL-6 and IL-1b. 10,11 Increased levels of these cytokines in the oral fluids have been associated with the etiology of periodontal and peri-implant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…(kappa 0.86) blinded to the study groups assessed the peri-implant soft tissue inflammatory parameters. Peri-implant PD, 19 PI, 19 and BOP 19 were measured at 6 sites/implant (mesiobuccal, midbuccal, distobuccal, distopalatal/distolingual, midpalatal/midlingual, and mesiopalatal/mesiolingual). PD was measured using a standard probe (Hu-Friedy Manufacturing, Chicago, Illinois).…”
Section: Assessment Of Clinical and Radiographic Peri-implant Parammentioning
confidence: 99%
“…There is a general misconception that waterpipe smoking is less hazardous to health than conventional cigarette smoking as the water through which the waterpipe smoke bubbles filters most of the toxic chemicals present in smoke, such as carbon monoxide (CO), tar, and nicotine (7). However, it has been shown that individuals smoking waterpipes have oral and systemic health conditions similar to those of cigarette smokers, such as periodontal disease, asthma, respiratory infections, hypertension, and persistent coughing (7,8). To our knowledge, no previous studies have investigated peri-implant clinical and radiographic status among habitual waterpipe smokers (WS).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that further strategies be implemented to reduce the rate of smokers (cigarette and hookah) to decrease the rate of oral diseases. and this study is the first study in this regard, although studies have studied the association of hookah smoking on oral and periodontal diseases (24)(25)(26). Although hookah is smoked in some countries, its use is very prevalent among Iranians, especially youths (27).…”
Section: Discussionmentioning
confidence: 85%